Glucose dysregulation and repolarization variability markers are short-term mortality predictors in decompensated heart failure. Issue 3 (30th May 2022) - Piccirillo, Gianfranco; Moscucci, Federica; Carnovale, Myriam; Corrao, Andrea; Di Diego, Ilaria; Lospinuso, Ilaria; Sciomer, Susanna; Rossi, Pietro; Magrì, Damiano
Abstract : Objective: As recently reported, elevated fasting glucose plasma level constitutes a risk factor for 30-day total mortality in acutely decompensated chronic heart failure (CHF). Aim of this study was to evaluate the 30-day mortality risk in decompensated CHF patients by fasting glucose plasma level and some repolarization ECG markers. Method: A total of 164 decompensated CHF patients (M/F: 94/71; mean age, 83 ± 10 years) were studied; Tend (Te), QT interval (QT) and 5 min of ECG recordings were obtained, studying mean, SD and normalized index of the abovementioned ECG intervals. These repolarization variables and fasting glucose were analyzed to assess the 30-day mortality risk among these patients. Results: Thirty-day mortality rate was 21%, deceased subjects showed a significant increase in N terminal-pro-brain natriuretic peptide ( P < 0.001), higher sensitivity cardiac troponin, fasting glucose, creatinine clearance, QTSD, QTVN, Te mean, TeSD and TeVN than the survivals. Multivariable regression analysis reported that fasting glucose (hazard ratio, 1.59; 95% confidence interval, 1.09–2.10; P < 0.01), Te mean (hazard ratio, 1.03; 95% confidence interval, 1.01–1.05; P < 0.01) and QTSD (hazard ratio, 1.17; 95% confidence interval, 1.01–1.36; P < 0.05) were significantly related to higher mortality risk, whereas only fasting glucose (hazard ratio, 1.84; 95% confidence interval, 1.12–3.02; P < 0.05) and Te mean (hazard ratio, 1.07; 95% confidence interval, 1.02–1.11; P < 0.01) were associated to cardiovascular mortality. Conclusion: Data suggest that two simple, inexpensive, noninvasive markers, as fasting glucose and Te, were capable to stratify the short-term total and cardiovascular mortality risk in acutely decompensated CHF.